2010
DOI: 10.3109/0142159x.2010.528808
|View full text |Cite
|
Sign up to set email alerts
|

Triangulation of written assessments from patients, teachers and students: Useful for students and teachers?

Abstract: Background: Many medical students in general practice clerkships experience lack of observation-based feedback. The StudentPEP project combined written feedback from patients, observing teachers and students. Aim: This study analyzes the perceived usefulness of triangulated written feedback. Methods: A total of 71 general practitioners and 79 medical students at the University of Oslo completed project evaluation forms after a 6-week clerkship. A principal component analysis was performed to find structures wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 13 publications
1
11
1
Order By: Relevance
“…In our study, some students tended to underestimate their own performance, which is alignment with previous studies [ 4 , 43 ]. The patients’ scoring in the PFCP questionnaire were generally higher than the students’ own scoring, which has also been found in previous studies [ 4 , 23 ]. In general, the clinical supervisors’ scores were also often slightly higher than the students’ own scoring, which has been described in previous studies as well [ 4 ].…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…In our study, some students tended to underestimate their own performance, which is alignment with previous studies [ 4 , 43 ]. The patients’ scoring in the PFCP questionnaire were generally higher than the students’ own scoring, which has also been found in previous studies [ 4 , 23 ]. In general, the clinical supervisors’ scores were also often slightly higher than the students’ own scoring, which has been described in previous studies as well [ 4 ].…”
Section: Discussionsupporting
confidence: 87%
“…Only a few studies were found where different groups of participants used the same feedback questionnaire or evaluation form to provide feedback to a medical student about a specific encounter [ 21 , 22 ]. Previous studies in which medical students receive MSF are usually based on different questionnaires and evaluation forms embedded in different teaching and learning programmes [ 4 , 19 , 23 , 24 ]. This means that the feedback provided is usually anonymous, delayed and provided after numerous patient encounters [ 4 , 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…Feedback from patients has also been shown to be useful, although most ratings and comments received are positive and complimentary, as we have observed [37-39]. Receiving feedback directly from patients is also likely to increase students’ awareness of the patients’ perspective on illness [40]. There is little work on the use of administrators in assessing medical students, but we believe that including their opinions is important as it is fairly simple to do and allows observations on issues such as absence, lateness and respect for non-medical staff.…”
Section: Discussionmentioning
confidence: 79%
“…[ 10 ] When exploring the perceived usefulness of the tool, we found that patients’ evaluations increased students' awareness of the patient perspective, and a majority of the students considered the triangulated written feedback beneficial, although time-consuming. [ 12 ] The teachers’ attitudes to the tool strongly influenced the students’ views on how useful StudentPEP was. [ 12 ] The faculty thereafter decided to simplify the tool by not requiring the separate patient survey, but give priority to the five mandatory observations with written feedback from patients, students, and teachers.…”
Section: Introductionmentioning
confidence: 99%
“…[ 12 ] The teachers’ attitudes to the tool strongly influenced the students’ views on how useful StudentPEP was. [ 12 ] The faculty thereafter decided to simplify the tool by not requiring the separate patient survey, but give priority to the five mandatory observations with written feedback from patients, students, and teachers.…”
Section: Introductionmentioning
confidence: 99%